Winter Short-Pulse Radar Studies on the Tanana River, Alaska - Delaney, Allan J.; Arcone, Steven A.; Chacho, Edward F. (ARCTIC, 1990)
Subsurface profiles were obtained during airborne and surface short-pulse radar surveys along a winter roadway over the Tanana River near Fairbanks, Alaska. The roadway crossed ice-covered channels and intervening frozen channel bars. The airborne profiles were intended for ice thickness profiling but also revealed sporadic reflections from a deeper horizon beneath the bars. Later profiling from the surface recorded these deeper reflecting horizons in detail, and they were found to correspond with the base of seasonal frost, measured in drill holes. The sediments immediately beneath the frozen material were saturated and represented the top of a seasonally variable groundwater table confined and controlled by frost penetration. The profiles made from the surface also revealed reflections from the bottom of the ice and the channel bottom. However, no significant reflections were observed beneath the channel bottom; reflections from sloping horizons above and below the base of the frost in the bar may indicate alluvial bedding patterns in these deposits. Eleven holes were drilled along the roadway to determine ice thickness, water depth, frost depth and the depth to the river ice-alluvium contact. Wide-angle reflection and refraction soundings were also made to determine electrical properties of materials and to verify our depth interpretations from echo times. These observations indicate that the airborne technique provides an effective method of locating unfrozen channels and measuring the depth of frost penetration beneath bars. The surface surveys revealed additional data on sedimentary structure.